RESOURCE BASED ECONOMY AND DUTCH DISEASE: THE CASE OF MONGOLIA: Hong-Jin Kim - Hong-Jin Kim, (Acta Mongolica, 2012)
The Mongolian economy is highly dependent on mineral exports and has been governed by a history of pro-cyclical macroeconomic policies. Mongolia has demonstrated substantial economic growth resulting from the mining boom during the past several years. Indeed, mining, extraction, and exponaiion have been increasing substantially and have become leading sectors ofthe economy. Increased mining, extraction, and exponaiion have led to a huge influx of foreign exchange into the country, which, in turn, has created opportunities for the establishment of large-scale projects for developing the infrastructure and the social projects that contributed to national socioeconomic development. However, the aforementioned simultaneous developments in the mining sector, the infrastructure, and the social domain have also been accompanied by negative economic trends such as the decrease in the share ofthe GDP and total exports attributable to ihe non-mining tradable sector, the increase in overall price levels, and the appreciation in the real effective exchange rate.